Charles Bonnet syndrome among visually impaired military veterans: findings from a UK screening and survey study - Matthew Lee; Mariya Moosajee; Lee Jones; Sonali Dave; Lara Ditzel-Finn; Judith Potts; Nikki Heinze; Renata S M Gomes; Eunice S Y Tang (BMJ Open Ophthalmology)
Background/Aims Charles Bonnet syndrome (CBS) is a common complication of visual impairment. However, demographic and clinical characteristics may modify the prevalence and impact of the condition. The aim was to investigate the prevalence of CBS among visually impaired military veterans and the associated impact of visual hallucinations.Methods Cross-sectional screening and survey study of members at Blind Veterans UK, a national charity supporting ex-armed forces men and women with a registered visual impairment. Data were analysed using membership records followed by a prospective CBS screening measure and survey.Results 461 military veterans with CBS were identified from 4109 individual records, representing 11.2% (95% CI 10.2% to 12.2%) of the population. From this, 115 members (24.9%) participated in the survey. The average age was 82.5 (±12.3) years and 89.6% were male. The most common ophthalmic condition was age-related macular degeneration (58.3%) and participants had severely reduced visual acuity (average better eye 1.2 (±1.4) LogMAR). Reporting ‘bothersome’ hallucinations was associated with living with CBS for over 3 years (p=0.01) and hallucinating at least once per week (p=0.05). Diverting attention elsewhere was considered an effective relief strategy among 64.9% (95% CI 56.2% to 73.6%) of those who had used this. Fewer than half (44.3%) had disclosed their symptoms to a hospital doctor and corresponding clinical management was variable.Conclusion CBS was common among visually impaired military veterans and was associated with negative outcomes. However, limitations include identifying cases through retrospective screening and not controlling for visual acuity and rehabilitation. Findings may not generalise beyond veterans in the charity’s database. Yet, the findings yield evidence for a therapeutic benefit of relief strategies in managing symptoms and the need to promote dialogue about visual hallucinations between patients and clinicians.